2021
DOI: 10.1007/s00167-021-06567-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of typical pain patterns with SPECT/CT findings in unhappy patients after total knee arthroplasty

Abstract: Purpose The diagnostic process in patients after painful total knee arthroplasty (TKA) is challenging. The more clinical and radiological information about a patient with pain after TKA is included in the assessment, the more reliable and sustainable the advice regarding TKA revision can be. The primary aim was to investigate the position of TKA components and evaluate bone tracer uptake (BTU) using pre-revision SPECT/CT and correlate these findings with previously published pain patterns in pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The use of this image scheme was also important for defining particular BTU patterns associated with specific conditions, such as malpositioning of the components, maltracking, patellar overloading, patellar osteoarthritis and loosening, which led the clinician to change the initial diagnosis in up to 85% of the patients [ 40 , 41 , 46 ]. It is important to highlight a recent report by Mathis et al [ 21 ], which showed a significant correlation ( P < 0.05) between different patterns of BTU and the position of the TKA components together with different pain patterns, enhancing the importance of the component position as a potential source of pain in painful knee arthroplasty patients. The authors concluded that component positioning-related pathologies accounted for the greatest proportion of cases, followed by patella-related problems and instability.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The use of this image scheme was also important for defining particular BTU patterns associated with specific conditions, such as malpositioning of the components, maltracking, patellar overloading, patellar osteoarthritis and loosening, which led the clinician to change the initial diagnosis in up to 85% of the patients [ 40 , 41 , 46 ]. It is important to highlight a recent report by Mathis et al [ 21 ], which showed a significant correlation ( P < 0.05) between different patterns of BTU and the position of the TKA components together with different pain patterns, enhancing the importance of the component position as a potential source of pain in painful knee arthroplasty patients. The authors concluded that component positioning-related pathologies accounted for the greatest proportion of cases, followed by patella-related problems and instability.…”
Section: Discussionmentioning
confidence: 96%
“…The highest diagnostic accuracy for SPECT/CT in detecting loosening was reported by Abele et al and Bao et al [ 39 , 42 ], who used intraarticular administration of the radiotracer 99m Tc sulphur colloid with a sensitivity and negative predictive value of 100%, which was superior to other imaging methods. SPECT/CT was also able to identify other sources of pain, such as patellofemoral hyper pressure, instability and malalignment of the components, with findings confirmed by intraoperative or clinical follow-up [ 21 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found the increased bone tracer uptake (BTU) in single‐photon emission computed tomography/computed tomography (SPECT/CT) could be a valuable method for predicting residual pain following TKA [2, 31]. Furthermore, Mathis et al [20] demonstrated a significant correlation between the areas of increased BTU and pain patterns after TKA. Additionally, Slevin et al [34] suggested that SPECT/CT could be a valuable modality for diagnosing patellofemoral disorders after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…An increase of BTU in femoral or tibial regions could indicate signs of aseptic loosening or infection. [25,35,[51][52][53][54][55][56] Thirdly, there were no significant BTU differences between the alignment groups after TKA. This could be explained as follows.…”
Section: Discussionmentioning
confidence: 99%